Processing of self-initiated speech-sounds is different in musicians - Ott, Cyrill G.; Jäncke, Lutz (Frontiers in Human Neuroscience, 2013)
Musicians and musically untrained individuals have been shown to differ in a variety of functional brain processes such as auditory analysis and sensorimotor interaction. At the same time, internally operating forward models are assumed to enable the organism to discriminate the sensory outcomes of self-initiated actions from other sensory events by deriving predictions from efference copies of motor commands about forthcoming sensory consequences. As a consequence, sensory responses to stimuli that are triggered by a self-initiated motor act are suppressed relative to the same but externally-initiated stimuli, a phenomenon referred to as motor-induced suppression (MIS) of sensory cortical feedback. Moreover, MIS in the auditory domain has been shown to be modulated by the predictability of certain properties such as frequency or stimulus onset. The present study compares auditory processing of predictable and unpredictable self-initiated zero-delay speech sounds and piano tones between musicians and musical laymen by means of an event-related potential (ERP) and topographic pattern analysis (microstate analysis or EP mapping) approach. Taken together, our findings suggest that besides the known effect of MIS, internally operating forward models also facilitate early acoustic analysis of complex tones by means of faster processing time as indicated by shorter auditory N1-like microstate durations in the first ~ 200 ms after stimulus onset. In addition, musicians seem to profit from this facilitation also during the analysis of speech sounds as indicated by comparable auditory N1-like microstate duration patterns between speech and piano conditions. In contrast, non-musicians did not show such an effect.